Embedded ultra-high stability flexible transparent conductive films based on exfoliated graphene-silver nanowires-colorless polyimide. (5th March 2023) - Qian, Peng-Fei; Wang, Jing-Qi; Wang, Tao; Huai, Xuguo; Geng, Wen-Hao; Zhu, Qiangxia; Tian, Ying; Jing, Li-Chao; Bao, Ze-Long; Geng, Hong-Zhang
Abstract: Transparent conductive films with high stability were prepared by embedding silver nanowires in colorless polyimide and adding a protective layer of exfoliated graphene. The films exhibit great light transmission and conductivity with a sheet resistance of 22 Ω sq −1 at transmittance of 83%. Due to its special embedded structure, the conductive layer can withstand several peeling experiments without falling off. In addition, the most outstanding advantage is the ultra-high stability of the films, including high mechanical robustness, strong chemical corrosion resistance and high operating voltage capacity. The organic light-emitting diode devices prepared based on this transparent conductive electrode exhibit comparable efficiency to indium tin oxide (ITO) based devices, with C.E. max = 2.78 cd A −1, P −1 .E. max = 1.89 lm W −1, EQE max = 0.89%. Moreover, the efficiencies were even higher than that of ITO devices when the operating voltage of the device exceeds 5 V. The above performances show that the transparent conductive electrode based on this structure has high potential for application in organic electronic devices.